Effect of vitamin D deficiency on depressive symptoms in child and adolescent psychiatric patients: results of a randomized controlled trial - Libuda, Lars (Eur J Nutr, 2020)
PURPOSE: While observational studies revealed inverse associations between serum vitamin D levels [25(OH)D] and depression, randomized controlled trials (RCT) in children and adolescents are lacking. This RCT examined the effect of an untreated vitamin D deficiency compared to an immediate vitamin D(3) supplementation on depression scores in children and adolescents during standard day and in-patient psychiatric treatment. METHODS: Patients with vitamin D deficiency [25(OH)D ≤ 30 nmol/l] and at least mild depression [Beck Depression Inventory II (BDI-II) > 13] (n = 113) were 1:1 randomized into verum (VG; 2640 IU vitamin D(3)/d) or placebo group (PG) in a double-blind manner. During the intervention period of 28 days, both groups additionally received treatment as usual. BDI-II scores were assessed as primary outcome, DISYPS-II (Diagnostic System for Mental Disorders in Childhood and Adolescence, Self- and Parent Rating) and serum total 25(OH)D were secondary outcomes. RESULTS: At admission, 49.3% of the screened patients (n = 280) had vitamin D deficiency. Although the intervention led to a higher increase of 25(OH)D levels in the VG than in the PG (treatment difference: + 14 ng/ml; 95% CI 4.86–23.77; p = 0.003), the change in BDI-II scores did not differ (+ 1.3; 95% CI − 2.22 to 4.81; p = 0.466). In contrast, DISYPS parental ratings revealed pronounced improvements of depressive symptoms in the VG (− 0.68; 95% CI − 1.23 to − 0.13; p = 0.016). CONCLUSION: Whereas this study failed to show a vitamin D supplementation effect on self-rated depression in adolescent in- or daycare patients, parents reported less depressive symptoms in VG at the end of our study. Future trials should consider clinician-rated depressive symptoms as primary outcome. TRIAL REGISTRATION: “German Clinical Trials Register” (https://www.drks.de), registration number: DRKS00009758